High Voltage Gain of Non-Isolated Inductor-Less DC-DC Converter - Ponniran, Asmarashid (International Journal of Integrated Engineering, 2019)
The main purpose of this study is to analyze a multilevel DC-DC converter structure for achieving high voltage gain of DC-DC converter. The inductor-less multistage modular capacitor clamped DC-DC converter (IMMCCC) is one of the multilevel structure that can achieve the high voltage gain. In this circuit structure, the concept of charging and discharging capacitors is used in order to achieve high voltage gain regardless of the duty cycle influence. For a conventional DC-DC boost converter, the output voltage is depending on the duty cycle, where the high voltage gain is not practically achievable even though with high duty cycle. Thus, the multistage structure which is IMMCCC is selected in order to achieve the high voltage gain of DC-DC converter. In order to analyze and confirm principle of the designed converter, simulation and experimental works are conducted. Three structures i.e., one, two and three stages of the IMMCCC are designed and constructed. Based on the experimental results, the obtained output voltages are 60 V (boost ratio 2), 90 V (boost ratio 3) and 120 V (boost ratio 4) with the input voltage of 30 V. From the simulation and experimental results, the operation of the designed IMMCCC is confirmed.